Feminist economics editorial policies. (Feminist Economics, 2007)
The article discusses the editorial policies of the journal "Feminist Economics." These editorial policies include Policy on Statistical Reporting, Policy on Orienting Papers for an International Audience, Policy on Papers Using Information From Human Participants. The Policy on Statistical Reporting requires that discussions of statistical results report standard errors rather than t-statistics. Moreover, these policies should be followed strictly when submitting manuscripts.